Social Support Patterns of Parents In The Education Process of Children In Pondok Pesantren (A Phenomenological Study at Pondok Pesantren Tebuireng, Jombang) - Pahlawanita Damayanti, Dimas; Zulkarnain, Zulkarnain; Wahyuni, Sri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research aims to analyze parental social support for children who reside at Pondok Pesantren Tebuireng in Jombang, focusing on parental support motives, forms of social support, and efforts to enhance this support. The research methodology employed a qualitative interpretative phenomenology approach with data collection techniques including interviews, participatory observation, and document analysis. The study’s findings reveal two main factors in parental support motives: the development of Islamic education and the significance of historical figures. The development of Islamic education encompasses comprehensive religious education, character development, and the facilitation of talent development. The role of historical figures involves reverence for figures such as KH. Hasyim Asy’ari and Abdurrahman Wahid, as well as the connection to Nahdlatul Ulama and the Ahlussunah Wal-Jamaah tradition. Parental social support includes four main aspects: academic support, motivational support, emotional-psychological support, and instrumental support. This encompasses monitoring academic progress, providing motivation, fostering emotional bonds, and offering financial assistance. Efforts to enhance parental support involve intensive communication, collaboration with teachers, creating a supportive learning environment, providing positive reinforcement, and offering specialized support during puberty transitions. Parents play a crucial role in supporting the adaptation and academic achievement of their children in the pesantren.